Pembelajaran Literasi untuk Meningkatkan Kemampuan Membaca Al Qur’an Hadits Siswa di Ma Nurul Qur’an Bendung Jogoroto Jombang - Muhammad Budi Arif (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Education is tailored to the real needs that learners want, the potential and culture of the community. Various educational problems that exist in Indonesia require the efforts of the steps of consistent basic refinement and systematic paradigm of education. This enhancement is an education that can develop the potential of students to be brave to face the challenges of life as well as global challenges, without any sense of distress, our education should be able to encourage students to have knowledge, skills, have high confidence that can quickly adapt to the environment. The purpose of this study are: 1) To know the literacy learning in MA Nurul Qur'an Bendung Jogoroto Jombang. 2) 2. To Know the ability to read Al Qur'an Hadith students in MA Nurul Qur'an Bendung Jogoroto Jombang. 3) 3. To know the implementation of Literacy Learning to Increase the Ability of Reading Al Qur'an Hadits Students in Ma Nurul Qur'an Bendung Jogoroto Jombang. Population taken is the students MA Nurul Qur'an Bendung Jogoroto Jombang Lesson 2016/2017 Year which amounted to 112 people. In this study the authors use Probability Sampling technique. taken as sample is as much as 88 respondents. Hypothesis test A simple linear regression analysis consists of one independent variable (predictor) and one dependent variable (response), with the equation: Y = a + bX. From the results of research that the authors do in the field can the authors conclude as follows: 1) Learning literacy in MA Nurul Qur'an Jogoroto Bend Jombang pretty good. 2) Improved ability to read Al Qur'an Hadith students in MA Nurul Qur'an Jogoroto Bend Jombang pretty good. 3) There is a significant positive effect of learning literacy on improving the ability of reading Al Qur'an Hadith students on MA Nurul Qur'an Bendung Jogoroto Jombang.